2019
DOI: 10.1002/jia2.25302
|View full text |Cite
|
Sign up to set email alerts
|

Contextual drivers of HIV risk among young African women

Abstract: Introduction Significant progress has been made in the African HIV pandemic; however, the pace of incidence decline has slowed or stalled in many East and Southern African countries, especially among young women. This stall is worrying because many countries have burgeoning youth populations. There is an important window of opportunity to halt the epidemic as well as the potential for millions more infections if primary prevention efforts are not strengthened. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 92 publications
(120 reference statements)
0
11
0
Order By: Relevance
“…In this supplement, we have brought together a number of articles that build on some of the discussions at that meeting, representing a variety of disciplinary perspectives. Mojola and Wamoyi start with a narrative and insightful review into the drivers of HIV risk among young African women , and use insights from their own and others’ research to show how epidemiological, gender‐normative and environmental contexts interact to drive hyperendemics of HIV, and how similar factors undermine preventive interventions. Their deep descriptions of how social drivers result in risky settings and behaviours are then used to suggest how that context can inform intervention planning.…”
Section: Banbury Meeting and Supplementmentioning
confidence: 99%
“…In this supplement, we have brought together a number of articles that build on some of the discussions at that meeting, representing a variety of disciplinary perspectives. Mojola and Wamoyi start with a narrative and insightful review into the drivers of HIV risk among young African women , and use insights from their own and others’ research to show how epidemiological, gender‐normative and environmental contexts interact to drive hyperendemics of HIV, and how similar factors undermine preventive interventions. Their deep descriptions of how social drivers result in risky settings and behaviours are then used to suggest how that context can inform intervention planning.…”
Section: Banbury Meeting and Supplementmentioning
confidence: 99%
“…Aspirations which closely resemble an individual's living standards can disincentivise change, while aspirations too far removed from current living standards can disempower individuals to change (Appadurai, 2004;Ray, 2006). Adolescents' aspirations and hopes (realistic plans/expectations) evolve and increasingly shape their life choices (Appadurai, 2004;Davids et al, 2017) including those related to their sexual behaviours (Kagan et al, 2012), as they are exposed to various structural factors (Mojola & Wamoyi, 2019) and through social interactions with peers (Appadurai, 2004).…”
Section: Theoretical Framework: Aspirations Theory and Agencymentioning
confidence: 99%
“…Similarly, public health historian Samuel Kelton Roberts detailed how racial residential segregation drove TB infection and mortality among African-Americans in 20th century Baltimore via impacts on housing, workplace conditions, medical treatment, and public health policies [ 50 ]. These mechanisms have been repeatedly articulated in narrative histories, risk-factor analyses, and mixed-methods studies of many infections including cholera [ 51 ], HIV [ 52 , 53 ], and malaria [ 54 , 55 ]. Clouston and colleagues found that while high-income US counties were the first to see an introduction of SARS-CoV-2 infection, the pace of infection and mortality in these counties quickly slowed through NPIs (e.g., work from home, school closures).…”
Section: Introductionmentioning
confidence: 99%